Is an anodizing coating associated to the photobiomodulation able to optimize bone healing in ovariectomized animal model? - Polo, Tárik Ocon Braga [UNESP]; Momesso, Gustavo Antônio Correa [UNESP]; Silva, William Phillip Pereira [UNESP]; Santos, Anderson Maikon de Souza [UNESP]; Fonseca-Santos, João Matheus [UNESP]; da Cruz, Nilson Cristino [UNESP]; Barão, Valentim A.R.; Garcia, Valdir Gouveia [UNESP]; Theodoro, Letícia Helena [UNESP]; Faverani, Leonardo P. [UNESP] (Elsevier, 2021)
This in vivo study investigated whether the bioactivity of anodizing coating, produced by plasma electrolytic oxidation (PEO), on mini-plate in femur fracture could be improved with the association of photobiomodulation (PBM) therapy. From the 20 ovariectomized Wistar female rats, 8 were used for model characterization, and the remaining 12 were divided into four groups according to the use of PBM therapy by diode laser (808 nm; power: 100 mW; energy: 6.0 J; energy density: 212 J/cm2; power density: 3.5 W/cm2) and the type of mini-plate surface (commercially pure titanium mini-plate -cpTi- and PEO-treated mini-plate) as follow: cpTi; PEO; cpTi/PBM; and PEO/PBM. After 60 days of surgery, fracture healing underwent microstructural, bone turnover, histometric, and histologic adjacent muscle analysis. Animals of groups with PEO and PBM showed greater fracture healing than cpTi control group under histometric and microstructural analysis (P < 0.05); however, bone turnover was just improved in PBM's groups (P < 0.05). there was no difference between cpTi and PEO without PBM (P > 0.05). Adjacent muscle analysis showed no metallic particles or muscle alterations in all groups. PEO and PBM are effective strategies for bone repair in fractures, however their association does not provide additional advantages.
Keywords: Anodic films; Bone; Fractures; Laser; Oxide coating